ENVISAGING AND ENFORCING INDIVIDUAL, AGGREGATED, COLLECTIVE, DIFFUSE, AND GLOBAL RIGHTS RELATING TO CLIMATE CHANGE, THE GREENHOUSE EFFECT, AND THE ENVIRONMENT - Oquendo, Ángel (Revista Eletrônica de Direito Processual, 2021)
The 2015 Paris Agreement, complementing the United Nations Framework Convention on Climate Change, showcases an impressive consensus on climatological rhetoric. Thereby, it will contribute certainly neither to achieving its overall objectives on temperature nor to redressing any of the resulting “loss [or] damage” yet possibly to continuing the worldwide dialogue on the environment or on ecological entitlements. This paper will dissect and categorize these. It will conclude that the framers essentially kept the conversation going, nationally and internationally, encouraging the establishment, the adjudicatory branch, and the public to resume the conceptual or practical advancement on the topic